Age-Inclusive ICT Innovation for Service Delivery in South Africa A Developing Country Perspective - Roos, Vera; Hoffman, Jaco (Springer International Publishing : Imprint: Springer, 2022)
This open access book presents a step-by-step journey to address the problem of ineffective service delivery by local government that led to the leveraging of new technology to benefit older individuals. Based in South Africa, this exploration is in one sense peculiar to its setting-a developing country with huge inequalities-but the story goes beyond the immediate geographical setting of (South) Africa and transcends the temporal aspect of ICT technology. It reflects on older persons' participation, negotiation, and transition in the development of a technology artefact that offers the potential to access services and activities, and to participate in an inclusive society for all ages. This theme has wider resonance, and demonstrates a phenomenon witnessed in different ways and stages across the globe: cohorts of older persons negotiating waves of updated and new technologies. This edited volume details a workable, transdisciplinary and relational approach to 21st-century ICT innovation that helps create a technology artefact tailored for purpose. Worldwide, it is anticipated that care needs of older populations will outstrip available resources. Sub-Saharan Africa lacks relevant long-term care systems for older persons, and technology could play a crucial role in supporting families, communities and government in vital care management. This volume addresses, in three parts, the under-explored topic of age-inclusive ICT development and use in resource-poor countries. Part 1, Context and Project Background, sets out ICT service delivery to older persons globally and within South Africa, drawing on guiding legislative frameworks. It discusses the we-DELIVER project as an example of developing and applying age-inclusive technology in developing countries. Part 2, Principles, Process and Applications, proposes situationally and relationally informed ethical conduct in applying community-based research; the development of a questionnaire and application to present first-time baseline findings of older South Africans' cell phone use, highlighting its intergenerational facilitation. The development of the Yabelana (alluding to 'sharing') ecosystem (consisting of a website, an app, and an unstructured supplementary service data (USSD) code) turned out to be a first of its kind: a digital self-sustaining technology artefact that serves as an eDirectory to provide information about local services or events for (but not exclusively) older individuals. Part 3, Critical Reflections and the Way Forward, considers the inclusion of marginalized older individuals and the future of ICT and cell phone technology to inform research, practice, and policy. This topical edited volume is of interest to social science researchers and students as well as policy makers and practitioners dealing with the life course, ageing and age care, intergenerational issues, technology, social policy, and social work.